Improvement of spinal alignment and quality of life after corrective surgery for spinal kyphosis in patients with osteoporosis: a comparative study with non-operated patients. Issue 11 (November 2015) - Miyakoshi, N.; Hongo, M.; Kobayashi, T.; Abe, T.; Abe, E.; Shimada, Y.
Abstract Summary This study evaluated changes in spinal alignment and quality of life (QOL) after corrective spinal surgery for patients with postmenopausal osteoporosis and spinal kyphosis. Spinal global alignment and QOL were significantly improved after corrective spinal surgery but did not reach the level of non-operated controls. Introduction With the increased aging of society, the demand for corrective spinal instrumentation for spinal kyphosis in osteoporotic patients is increasing. However, previous studies have not focused on the improvement of quality of life (QOL) after corrective spinal surgery in patients with osteoporosis, compared to non-operated control patients. The purposes of this study were thus to evaluate changes in spinal alignment and QOL after corrective spinal instrumentation for patients with osteoporosis and spinal kyphosis and to compare these results with non-operated patients. Methods Participants comprised 39 patients with postmenopausal osteoporosis ≥50 years old who underwent corrective spinal surgery using multilevel posterior lumbar interbody fusion (PLIF) for symptomatic thoracolumbar or lumbar kyphosis, and 82 age-matched patients with postmenopausal osteoporosis without prevalent vertebral fractures. Spinopelvic parameters were evaluated with standing lateral spine radiography, and QOL was evaluated with the Japanese Osteoporosis QOL Questionnaire (JOQOL), SF-36, and Roland-Morris Disability Questionnaire (RDQ). Results Lumbar kyphosis angle, sagittal vertical axis, and pelvic tilt were significantly improved postoperatively. QOL evaluated with all three questionnaires also significantly improved after 6 months postoperatively, particularly in domain and subscale scores for pain and general/mental health. However, these radiographic parameters, total JOQOL score, SF-36 physical component summary score, and RDQ score were significantly inferior compared with non-operated controls. Conclusions The results indicate that spinal global alignment and QOL were significantly improved after corrective spinal surgery using multilevel PLIF for patients with osteoporosis and spinal kyphosis but did not reach the level of non-operated controls.